Nuclear magnetic resonance spectroscopic analysis of salivary metabolome in sarcoidosis. - Duchemann, Boris; Triba, Mohammed Nawfal; Guez, Dominique; Rzeznik, Matthias; Savarin, Philippe; Nunes, Hilario; Valeyre, Dominique; Bernaudin, Jean-François; Le Moyec, Laurence (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Sarcoidosis is a systemic granulomatous disease of unknown cause which has diverse clinical impacts, ranging from benign to very severe, which may therefore require systemic treatment. Only a few tools are currently available to monitor management in these patients. Objectives: As sarcoidosis is known to affect salivary glands, we hypothesized that analysis of saliva could reveal valuable biomarkers for disease management. We designed a comparative analysis of salivary metabolomics in patients and controls using Nuclear Magnetic Resonance (NMR). Methods: Metabolomic profiles of saliva collected from 24 sarcoidosis patients and 45 controls were obtained by proton NMR spectroscopy with multivariate statistical analysis, followed by metabolite identification and pathway analysis. Oral and dental examinations were performed concomitantly, together with assessment of smoking habits. Results: A predictive salivary metabolomic signature associated with sarcoidosis was computed with the Orthogonal Partial least squares discriminant analysis (OPLS) model. Six metabolites were altered in samples from sarcoidosis patients compared to controls, including decreased levels of methanol and butyrate and increased levels of lactate, acetate and N-butyrate. Conclusion: This study showed that NMR metabolomics can discriminate saliva samples from sarcoidosis patients and controls. According to these preliminary results, saliva studies in sarcoidosis patients would be particularly useful to identify potentially relevant biomarkers. A study based on a larger number of patients at different stages of the disease or with treated patients is needed to assess the clinical relevance of NMR metabolomics in sarcoidosis.